Exercise blood-drop metabolic profiling links metabolism with perceived exertion - Opialla, Tobias; Gollasch, Benjamin; Kuich, Peter H. J. L.; Klug, Lars; Rahn, Gabriele; Busjahn, Andreas; Spuler, Simone; Boschmann, Michael; Kirwan, Jennifer A.; Luft, Friedrich C.; Kempa, Stefan (Frontiers in Molecular Biosciences, 2022)
Background Assessing detailed metabolism in exercising persons minute-to-minute has not been possible. We developed a single “drop-of-blood” platform to fulfill that need. Our study aimed not only to demonstrate the utility of our methodology, but also to give insights into unknown mechanisms and new directions. Methods We developed a platform, based on gas chromatography and mass spectrometry, to assess metabolism from a single drop of blood. We first observed a single volunteer who ran 13 km in 30 min. We particularly monitored perceived exertion (RPE). We observed that 2,3-bisphosphoglycerate peaked at RPE in this subject. We next expanded these findings to women and men volunteers who performed an RPE-based exercise protocol to RPE at FiO2 20.9% or FiO2 14.5% in random order. Results At 6 km, our subject reached his maximum relative perceived exertion (RPE); however, he continued running, felt better, and finished his run. Lactate levels had stably increased by 2 km, ketoacids increased gradually until the run’s end, while the hypoxia marker, 2,3 bisphosphoglycerate, peaked at maximum RPE. In our normal volunteers, the changes in lactate, pyruvate, β hydroxybutyrate and α hydroxybutyrate were not identical, but similar to our model proband runner. Conclusions Glucose availability was not the limiting factor, as glucose availability increased towards exercise end in highly exerted subjects. Instead, the tricarboxylic acid→oxphos pathway, lactate clearance, and thus and the oxidative capacity appeared to be the defining elements in confronting maximal exertion. These ideas must be tested further in more definitive studies. Our preliminary work suggests that our single-drop methodology could be of great utility in studying exercise physiology.